Pengembangan Multimedia Interaktif Canva Dan Wordwall Pada Pembelajaran Matematika Materi Bangun Datar di Kelas IV Sekolah Dasar - Sri Mutiara; Syafri Ahmad (Universitas Negeri Padang, 2025)
This study was motivated by the limited use of interactive media in elementary Mathematics learning, which restricts students’ motivation and engagement. The research aimed to develop interactive multimedia for fourth-grade Mathematics learning that meets criteria of validity, practicality, and effectiveness. Using a Research and Development approach, the study employed the ADDIE model through analysis, design, development, implementation, and evaluation stages. Data were collected from expert validation sheets, practicality questionnaires, and pretest– posttest assessments, and analyzed using validity, practicality, and effectiveness measures. Results showed that teacher-centered instruction and minimal media variation reduced student participation. The design phase produced multimedia adapted to learners’ characteristics. Expert validation indicated high validity, with scores of 94 percent for material, 87.5 percent for media, and 96 percent for language. Practicality testing showed very practical use, with scores of 96 percent from teachers and 95 percent from students. Effectiveness testing indicated strong learning improvement, with an N-Gain of 83 percent and an increase from 46.0 to 90.2. Overall, the multimedia developed is valid, practical, and effective, encouraging educators to adopt interactive media to enhance meaningful learning.